EFFECTS OF ELECTRONIC PROCUREMENT ON EFFICIENCY AND TRANSPARENCY IN HEALTH SECTOR PROJECTS: EVIDENCE FROM PRIMARY HEALTH CARE FACILITY UPGRADING IN DELTA STATE, NIGERIA - Micheal Ejiofor Uduje; Joachim Chinonyerem Osuagwu; Magdalene Nkeiru Akanbi (World Journal of Advanced Research and Reviews, 2026)
Public procurement in developing countries has long been undermined by inefficiency, weak transparency and limited accountability, and these weaknesses are especially costly in the health sector, where procurement outcomes translate directly into the availability of medicines, equipment and functioning facilities. Electronic procurement (e-procurement) has been widely promoted as a governance response, yet empirical evidence on its influence within sector-specific, sub-national health projects in Nigeria remains limited. This study assessed the effect of e-procurement adoption on procurement efficiency and transparency in the ongoing upgrading of Primary Health Care (PHC) facilities in Delta State, Nigeria. A quantitative cross-sectional survey design was adopted. From an accessible population of 174 procurement-related personnel across six health-related Ministries, Departments and Agencies, a stratified random sample yielded 104 valid responses to a structured, five-point Likert-scale questionnaire (Cronbach's alpha 0.78-0.86). Data were analysed using descriptive statistics and Pearson Product Moment Correlation, corroborated by Spearman's rho and Kendall's tau-b, at the 0.05 significance level. E-tendering, e-bidding, e-invoicing/e-payment and e-contracting each showed a statistically significant positive relationship with procurement efficiency and transparency outcomes (p < 0.01), with e-invoicing/e-payment recording the strongest effect on financial governance indicators. ICT infrastructure and digital readiness correlated significantly with some components but not others, indicating that infrastructure alone does not guarantee effective implementation. The study concludes that e-procurement components meaningfully improve efficiency and transparency in health-sector project delivery, but that these gains are constrained by uneven ICT infrastructure and staff digital competence, which require complementary institutional investment.